1D Basin Modeling and Geochemical Analysis of Source Rock The Arafura Basin - Mamengko, David Victor; Mamengko, Michael Davidjoy Hamonangan; Setyowati , Tri Peni; Tandirerung, Restu (Scientific Contributions Oil and Gas, 2026)
The Arafura Basin is a frontier basin with significant hydrocarbon potential that remains poorly understood, particularly regarding source rock effectiveness across different structural settings. This study evaluates source rock potential, geochemical characteristics, and thermal maturity history using geochemical data and 1D basin modeling from five exploration wells (ABDX-1, BRX-1, KBX-1, KLX-1, and BBX-1). The analysis identifies several potential source rock intervals ranging from Permian, Jurassic, Cretaceous, to Tertiary ages. Geochemical evaluation reveals a stark contrast between depocenters and structural highs. Wells in the northern and southern depocenters (ABDX-1 and KLX-1) contain source rocks of fair to excellent quality that have reached optimal thermal maturity phases, ranging from peak to late mature. Conversely, wells in the structural high areas (BRX-1, KBX-1, and BBX-1) are to be non-generative as all source rock intervals remain immature due to insufficient burial history. Thermal history reconstruction indicates that the main phase of hydrocarbon generation occurred in the Neogene, triggered by a surge in sedimentation rates in response to the Melanesian Orogeny. This study concludes that exploration in the structural highs of the Arafura Basin carries high source rock risk, and successful hydrocarbon accumulation in these areas relies heavily on lateral migration from active hydrocarbon kitchens developing in the northern and southern depocenters.